The relationship of intimate partner violence on depression: the mediating role of perceived social support and the moderating role of the Big Five personality - Luo, Zhenni; Guan, Yan; Li, Yun; Xu, Weihong; Li, Lu; Liu, Siyuan; Zhou, Haozheng; Yin, Xuanhao; Wu, Yibo; Chen, Jiangyun (Frontiers in Public Health, 2024)
Introduction This study aimed to explore the influence of Intimate Partner Violence (IPV) on depression, the mediating role of social support, and the moderating role of the Big Five personality traits in the relationship between social support and depression. Methods Participants were recruited from Mainland China, using a stratified random sampling and quota sampling method. From June to August 2022, a diverse group of 21,916 participants (ranging from 12 to 100 years old) completed the Intimate Partner Violence Scale, Patient Health Questionnaire, Perceived Social Support Scale, and Big Five Inventory-Short Version. Results IPV was significantly positively correlated with depression and significantly negatively correlated with perceived social support. Perceived social support plays a mediating role in the link between IPV and depression. Discussion Healthcare workers should assess social support and provide adequate care or recommendations for increasing social support when patients with IPV report depressive symptoms. Patients can be coached by professionals to improve their resiliency by developing or nurturing more optimistic personality traits.